PENGARUH NET PROFIT MARGIN (NPM), RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR CONSUMER GOODS DI BURSA EFEK INDONESIA (BEI) - Nurhaini Nurhaini; Elia Kusumawati (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2020)
This study aims to analyze the effect of Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE) on the stock returns of consumer goods sector companies on the Indonesia Stock Exchange (BEI) 2014-2019 period. The sample of this study consisted of 9 (nine) consumer goods sector companies on the Indonesia Stock Exchange (BEI) for the 2014-2019 period using purposive sampling as the sampling method.  The data of this study used secondary data and the analysis method used was multiple linear regression analysis using the application of Statistical Product and Service Solution (SPSS) version 22 to test the effect of independent variables on the dependent variable. With the t test to determine the effect partially and the F test to determine the effect simultaneously and the coefficient of determination to determine the ability of independent variables in explaining the dependent variable.  The results of this study indicate that partially Net Profit Margin (NPM) has a significant effect on Stock Returns, this is evidenced by a significance value smaller than the probability value, namely 0.003 0.05 and t count t table (-3.174 2.00758). Partially, Return On Assets (ROA) has no significant effect on Stock Returns, this is evidenced by a significance value greater than the probability value, namely 0.769 0.05 and t count t table (-0,296 2.00758).  Partially, Return on Equity (ROE) has a significant effect on Stock Return, this is evidenced by the significance value is smaller than the probability value, namely 0.002 0.05 and t count t table (3.309 2.00758). And simultaneously Net Profit Margin (NPM), Return On Assets (ROA) and Return On Equity (ROE) have a significant effect on Stock Returns, this is evidenced by a significance value smaller than the probability value, namely 0.012 0.05 and F count   F table (4.298 2.79).